HUBUNGAN ASUPAN GIZI SAHUR DENGAN KONSENTRASI BELAJAR PADA ANAK USIA SEKOLAH MADRASAH IBTIDAIYAH AS-SALAAMAH DI PAMULANG KOTA TANGERANG SELATAN - Handayani, Maulina; Tiras, Renada Octora; Ernawati, Ernawati; Pelawati, Ratna; Damiati, Nia (NURSE: Journal of Nursing and Health Science, 2025)
Background: Good nutritional intake will meet the needs of the brain to undergo school-age children's activities, if the brain meets its needs, learning concentration will also be good in line with Maslow's theory of the first and fourth hierarchies. Purpose: to determine the relationship between nutritional intake and concentration in school-age children MI As-Salaamah Pamulang, South Tangerang city Methods: Quantitative with a cross sectional approach, sample determination using simple random sampling. The instruments used are the Food Record Form to assess the variables of dawn nutritional intake and the Concentration Exercise Grid to assess concentration in children, the calculation of nutritional intake is carried out with the help of nutrisurvey software and based on the nutritional adequacy rate according to the Ministry of Health in 2019, Analysis using the spearmen rank test The number of samples taken was 88 samples.  Results: The results showed that there was a relationship between nutritional intake at dawn with learning concentration in school-age children (p-value = 0.008) with a value of r = 0.281 which means there is a sufficient relationship, that the better the nutritional intake at dawn the better the concentration in children. There are 84.1% good nutritional intake and 15.9% poor nutritional intake, also there are 76.1% good learning concentration level and 23.8% poor concentration.